CALCULATION OF PRODUCTION COST IN UD. USAHA BARU WITH FULL COSTING METHOD - Suprianto Suprianto; Bina Andari; Yely Sulistyawati (JARES (Journal of Academic Research and Sciences), 2019)
This study aims to evaluate the calculation of cost of production. The accuracy of the calculation of cost of production is influenced by the suitability in the accumulation and calculation of production costs which includes the cost of raw materials, direct labor costs and other costs (factory overhead costs). This research was conducted at UKM UD. Usaha Baru which aims to determine the calculation of cost of production at UD. Usaha Baru and to find out whether the calculation of cost of production is in accordance with the full costing method. The technique (method) of data analysis used in this study is quantitative analysis. Data collection techniques use interview techniques directly to obtain information from the number of units of monthly production, raw material costs, direct labor costs, and factory overhead costs, as well as other information relating to the calculation of cost of production. Based on the evaluation results for the calculation of raw material costs and labor costs are in accordance with the full costing method. However, the calculation of factory overhead costs is not in accordance with the full costing method because there are costs that have not been included in the calculation of production costs.